Kaitocephalin Antagonism of Glutamate Receptors Expressed in Xenopus Oocytes - Limon, Agenor (American Chemical Society, 2009)
[Image: see text] Kaitocephalin is the first discovered natural toxin with protective properties against excitotoxic death of cultured neurons induced by N-methyl-d-aspartate (NMDA) or α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA)/kainic acid (kainate, KA) receptors. Nevertheless, the effects of kaitocephalin on the function of these receptors were unknown. In this work, we report some pharmacological properties of synthetic (−)-kaitocephalin on rat brain glutamate receptors expressed in Xenopus laevis oocytes and on the homomeric AMPA-type GluR3 and KA-type GluR6 receptors. Kaitocephalin was found to be a more potent antagonist of NMDA receptors (IC(50) = 75 ± 9 nM) than of AMPA receptors from cerebral cortex (IC(50) = 242 ± 37 nM) and from homomeric GluR3 subunits (IC(50) = 502 ± 55 nM). Moreover, kaitocephalin is a weak antagonist of the KA-type receptor GluR6 (IC(50) ∼ 100 μM) and of metabotropic (IC(50) > 100 μM) glutamate receptors expressed by rat brain mRNA.